Naloxone administration by law enforcement officers in New York State (2015-2020) - Elham Pourtaher; Emily R. Payne; Nicole Fera; Kirsten Rowe; Shu-Yin John Leung; Sharon Stancliff; Mark Hammer; Joshua Vinehout; Michael W. Dailey (BMC, 2022)
Abstract Background The COVID-19 pandemic has amplified the need for wide deployment of effective harm reduction strategies in preventing opioid overdose mortality. Placing naloxone in the hands of key responders, including law enforcement officers who are often first on the scene of a suspected overdose, is one such strategy. New York State (NYS) was one of the first states to implement a statewide law enforcement naloxone administration program. This article provides an overview of the law enforcement administration of naloxone in NYS between 2015 and 2020 and highlights key characteristics of over 9000 opioid overdose reversal events. Methods Data in naloxone usage report forms completed by police officers were compiled and analyzed. Data included 9133 naloxone administration reports by 5835 unique officers located in 60 counties across NYS. Descriptive statistics were used to examine attributes of the aided individuals, including differences between fatal and non-fatal incidents. Additional descriptive analyses were conducted for incidents in which law enforcement officers arrived first at the scene of suspected overdose. Comparisons were made to examine year-over-year trends in administration as naloxone formulations were changed. Quantitative analysis was supplemented by content analysis of officers' notes (n = 2192). Results In 85.9% of cases, law enforcement officers arrived at the scene of a suspected overdose prior to emergency medical services (EMS) personnel. These officers assessed the likelihood of an opioid overdose having occurred based on the aided person's breathing status and other information obtained on the scene. They administered an average of 2 doses of naloxone to aided individuals. In 36.8% of cases, they reported additional administration of naloxone by other responders including EMS, fire departments, and laypersons. Data indicated the aided survived the suspected overdose in 87.4% of cases. Conclusions With appropriate training, law enforcement personnel were able to recognize opioid overdoses and prevent fatalities by administering naloxone and carrying out time-sensitive medical interventions. These officers provided life-saving services to aided individuals alongside other responders including EMS, fire departments, and bystanders. Further expansion of law enforcement naloxone administration nationally and internationally could help decrease opioid overdose mortality.